Animal Assisted Therapy (AAT) Program As a Useful Adjunct to Conventional Psychosocial Rehabilitation for Patients with Schizophrenia: Results of a Small-scale Randomized Controlled Trial - Calvo, Paula; Fortuny, Joan R.; Guzmán, Sergio; Macías, Cristina; Bowen, Jonathan; García, María L.; Orejas, Olivia; Molins, Ferran; Tvarijonaviciute, Asta; Cerón, José J.; Bulbena, Antoni; Fatjó, Jaume (Frontiers in Psychology, 2016)
Currently, one of the main objectives of human-animal interaction research is to demonstrate the benefits of animal-assisted therapy (AAT) for specific profiles of patients or participants. The aim of this study is to assess the effect of an AAT program as an adjunct to a conventional 6-month psychosocial rehabilitation program for people with schizophrenia. Our hypothesis is that the inclusion of AAT into psychosocial rehabilitation would contribute positively to the impact of the overall program on symptomology and quality of life, and that AAT would be a positive experience for patients. To test these hypotheses, we compared pre-program with post-program scores for the Positive and Negative Syndrome Scale (PANSS) and the EuroQoL-5 dimensions questionnaire (EuroQol-5D), pre-session with post-session salivary cortisol and alpha-amylase for the last four AAT sessions, and adherence rates between different elements of the program. We conducted a randomized, controlled study in a psychiatric care center in Spain. Twenty-two institutionalized patients with chronic schizophrenia completed the 6-month rehabilitation program, which included individual psychotherapy, group therapy, a functional program (intended to improve daily functioning), a community program (intended to facilitate community reintegration) and a family program. Each member of the control group (n=8) participated in one activity from a range of therapeutic activities that were part of the functional program. In place of this functional program activity, the AAT-treatment group (n=14) participated in twice-weekly 1-hour sessions of AAT. All participants received the same weekly total number of hours of rehabilitation. At the end of the program, both groups (control and AAT-treatment) showed significant improvements in positive and overall symptomatology, as measured with PANSS, but only the AAT-treatment group showed a significant improvement in negative symptomatology. Adherence to the AAT-treatment was significantly higher than overall adherence to the control group’s functional rehabilitation activities. Cortisol level was significantly reduced after participating in an AAT session, which could indicate that interaction with the therapy dogs reduced stress. In conclusion, the results of this small-scale RCT suggest that AAT could be considered a useful adjunct to conventional psychosocial rehabilitation for people with schizophrenia.